Modelling the Nordic Electricity Market using Infinite - Dimensional Stochastic PDE:s - Källén, Jonas (My University, 2016)
The prices of energy futures tend to have a noise structure that cannot easily be described with only a few factors. Therefore an infinite{dimensinoal model has been used to model and simulate the price of energy futures as paths of infinite{dimensional L2{ valued stochastic processes was made. The simulations agreed with previous attempts. The parameters of the model was then fitted to real price data. The results shared some features with the recorded prices.
Keywords: Matematik; Grundläggande vetenskaper; Mathematics; Basic Sciences